BUDAYA ORGANISASI PERSATUAN GURU REPUBLIK INDONESIA (PGRI) DI KABUPATEN KARANGANYAR (Studi Situs di Kabupaten Karanganyar) - SUDARYO , SUDARYO (2011)
The goal of reseac hos to get clear and accurate description about : (1) Characteristic of organization structure in increasing teacher professionalism, (2) Characteristic of work correlation of organization structure, (3) Characteristic of existence in developing work. The strategy used is ethnography. The characteris of Ethnography approach is the observer as an instrument ad as a student. Technique of collexting data include in dept interviewing, participant observer, documentation techinque. As informats are : The head of PGRI Karanganyar regency, branch leader of PGRI Mojogedang sub district, Group of honorary teacher Karanganyar Regency, The technique of data analysis used is the arrangement data technique in cities, such as : (1) The arrangement of contact diagram (2) The arrangement of check list matrix (3) Put the event in list and (4) Making and examining the prediction, and (5) Makin conclusing. The result of the research are : (1) The characteristic of organization o PGRI Karanganyar regency in increasing teacher professionalim, the organization structures suitable with Basi Bdget chapter IX section 26, proposed in section 25 and 26 ART, the committee is teacher and headmaster of elementary school, the decision is done by the committee of PGRI and lack of member aspiration (2) The characteristic of work correlation of organization structure in increasing teacher pofessionalism, such as (a) work draft is not socialized to he member specially for non active membersh such as the teacher at SMP and SMA/SMK. (b) all member deposed the contribution every month without knowing the use fund, (c) the member is not given a chance to follow anymore. (3) the characteristic of organization in developing work such as (a) we meet more teach in SMA and SMP who teach is not suitable with the education background, (b) give the existence in developing teacher professionalism but it is not maximal, (c) it's optimal in preparing teacher for mastering learning model such as CTL and PAKEM, (d) The management done is oriented by top management center management, PGRI hasn't been optimal to struggle, (It doesn't have enough financial tom train the teacher, (f) The prosperous of techer in doing the job hasn't been done by PGRI Karanganyar Regency anymore, (h) Ineffective sanksi given based on the teacher ethic code formulated by PGRI, and (i) communication channel between the PGRI Karanganyar member has done well with the meeting agenda/ committee meeting Karangnyar PGRI committee with sub distrct periodically.